The Relationship Between Immunoglobulin E Serum Levels And Age-Related Cataract - Meidina Rahmah; Alie Solahuddin (Sriwijaya Journal of Ophthalmology, 2019)
ABSTRACT Objective: To determine the relationship of serum IgE levels and age-related cataract at the Special Eye Hospital in Palembang. Methods: An observational study with cross-sectional design study was undertaken in October 2018 to May 2019 at the Special Eye Hospital in Palembang. There were 86 patients who met the inclusion and exclusion criteria. The independent variable in this study is the level of serum immunoglobulin E and the dependent variable is senile cataract. The data analysis has been done with diagnostic research by SPSS version 20.0 (SPSS, Inc Chicago, Illinois). Results: Thirty five people suffered from senile cataracts and fifty one people did not suffer from cataracts. The mean IgE level in senile cataract patients was 5.129 ± 1.588 ng /mL while in patients without cataracts it was 5.001 ± 1.564 ng/mL. There was no difference in IgE levels between senile cataract patients and patients without cataracts (p = 0.891). With statistical analysis using the ROC curve it was found that the IgE concentration cut off point was 5.046 ng/mL. There were 54.3% of senile cataract patients and 51% of patients without cataracts who had IgE levels > 5.046 ng/mL. Patients with IgE levels > 5.046 had an almost equal risk of senile cataracts compared to patients with IgE levels <5.046 (PR = 1.142 (CI95% 0.482 - 2.705; p = 0.935). Conclusion: There is no significant relationship between IgE levels and the incidence of senile cataracts.